Investigation of the Influence of Design Parameters on the Strength of Steel–Concrete Composite Shear Walls by Finite Element Simulations - Saavedra-Flores, E; Yanez-Cart, S; Guzman-Inostroza, C; Pina, J; Avudaiappan-, S (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
In this paper, the influence of design parameters on the strength of steel–concrete composite shear walls is investigated by means of finite element (FE) simulations. The shear wall typology studied in this paper consists of multiple composite plate shear wall-concrete encased on one or both sides of the plates. The FE models include contact technology to capture debonding between concrete and steel, tensile cracking in concrete, and large deflection theory involving local instabilities. Some design parameters considered in this work are the height-to-width ratio of the steel plates and their thickness, number of steel plates, the cross-section of the columns, and the height-to-width ratio of the shear wall. Furthermore, a sensitivity analysis of the normalised shear strength per unit cost of structure for these design parameters is also studied. Our numerical predictions are validated successfully with experimental data reported in the literature, revealing the predictive capabilities of the model. The present results provide further insight into the structural behavior of steel–concrete composite shear walls and pave the way for the future development of more efficient and innovative steel–concrete composite systems. © 2023 by the authors.